Impact of diamond seeding on the microstructural properties and thermal stability of GaN-on-diamond wafers for high-power electronic devices. (February 2017) - Liu, Dong; Francis, Daniel; Faili, Firooz; Middleton, Callum; Anaya, Julian; Pomeroy, James W.; Twitchen, Daniel J.; Kuball, Martin
Abstract: The impact of seeding of the diamond growth on the microstructural properties of GaN-on-diamond wafers was studied using in situ focused ion beam cross-sectioning and scanning electron microscopy imaging. Microstructural studies revealed that the seeding conditions are a critical parameter to obtain an optimal material, allowing the manufacture of GaN-on-diamond wafers with no microscopic defects and with structural stability under thermal annealing at 825 °C. The use of the right seeding conditions also results in homogeneous thermal properties across four inch GaN-on-diamond wafers, which is of critical importance for their use for ultra-high power microwave electronic devices. Graphical abstract: